Enhanced Anti-tumor of Pep-1 Modified Superparamagnetic Iron Oxide/PTX Loaded Polymer Nanoparticles - Wang, Baoyan; Wu, Weijun; Lu, Hongjin; Wang, Zhi; Xin, Hongliang (Frontiers in Pharmacology, 2019)
Abstract: Superparamagnetic iron-oxide nanoparticle (SPION) has gained tremendous attention for drug delivery applications due to their unique properties. In this study, we developed a dual targeted delivery system with paclitaxel (PTX) and SPION co-loaded PLGA nanoparticles which was modified with Pep-1 peptide (Pep-NP-SPION/PTX), aiming to achieve magnetic targeting and active targeting for tumor treatment. SPION was synthesized by a co-precipitation method and was then encapsulated with PTX simultaneously into PLGA nanoparticles. After that, the noncomplex was conjugated with Pep-1 through chemical modification. The resulting Pep-NP-SPION/PTX showed a spherical morphology and an average size around 100 nm. The enhancement cellular uptake of Pep-NP-SPION was demonstrated in in vitro by cell experiment. The IC50 value of Pep-NP-SPION/PTX and NP-SPION/PTX was determined to be 10.2 μg/mL and 19.4 μg/mL, respectively. Biodistribution study showed that obviously higher accumulation of Pep-NP-SPION was observed in tumor compared with that of non-targeting nanocomposite. Moreover, under the condition of magnetic field, both NP-SPION and Pep-NP-SPION exhibited much higher tumor distribution. Furthermore, Pep-NP-SPION/PTX presented desirable in vivo anti-tumor effect based on the active targeting and magnetic targeting characteristics. Taken together, Pep-NP-SPION/PTX could offer a magnetic targeting and receptor mediated targeting to enhance the anti-tumor outcome.